Quality of life and school environment in children with epilepsy - Barrios-Hernández, Yanquiel (2013)
The concept of quality of life is a term used to represent an important and interesting topic for current and future people. Having a chronic and non contagious disease such as epilepsy, affects the quality of life of people in one way or another. This article aims to explain the influence this disease has on the quality of life when it is suffered by school-age children. It also expects to demonstrate how family and school factors affect to the quality of life of children with epilepsy. Teaching professionals play a crucial role in this concern that the infant is not degraded by helping those children to not feel degraded by their environment; the explanation of this statement is one of the aspirations of this article.